Perivascular Wall Tumor in the Brain of a Dog - Margaret Cohn-Urbach; Annie Chen; Gary Haldorson; Stephanie Thomovsky (Case Reports in Veterinary Medicine)
A 9-year-old spayed female German shepherd mixed-breed dog presented for seizures. Magnetic resonance imaging revealed an irregularly marginated intraparenchymal cerebral mass. Microscopic examination of brain tissue collected postmortem demonstrated perivascular whorling and interwoven bundles of spindle-shaped cells. On immunohistochemistry, the tumor cells tested positive for vimentin and negative for factor VIII-related antigen, CD18, CD45, CD3, CD20, GFAP, S-100, and desmin. Immunohistochemistry results, in combination with histopathologic morphology, were suggestive of a perivascular wall tumor. To the authors’ knowledge, this is the first case report to utilize both histopathology and immunohistochemistry to describe a perivascular wall tumor in the brain of a dog.